Penghimpunan dan Distribusi Dana Zakat BAZNAS Daerah - Etti Eriani; Muhammad Arsyad; Rodame Monitorir Napitupulu (Journal of Islamic Social Finance Management, 2020)
AbstractThe aim of this research is to know zakat fund collection method and zakat fund distribution that carried out by BAZNAS in South Tapanuli Regency. This research approach is qualitative descriptive. The data source used is primary data. The data collection technique used by researchers is to use interviews, observation and structural documentation in the BAZNAS of South Tapanuli Regency.The results of this study indicate that the method of collecting zakat funds in the BAZNAS of South Tapanuli Regency uses the collection method in the form of cooperation with ASN (State Civil Apparatus), and some donors who give zakat to Amil are only for those who are aware of the obligation to pay zakat while the method of distributing zakat funds conducted by the BAZNAS of South Tapanuli Regency with direct methods that are consumptive and productive in four fields, namely: Economic, Education, Health and Social. Keywords: Zakat Fund Collection, Zakat Distribution, Regional BAZNAS Performance